Kreativitas Guru dalam Mengatasi Keterbatasan Media Pembelajaran Pada Pembelajaran IPA Di Kelas IV Sekolah Dasar - Farhan, Farhan; Rahalyu, Falsy; Adrias, Adrias; Syam, Salmaini Safitri (Publikasi dan UKI Toraja Press Universitas Kristen Indonesia Toraja, 2025)
This study aims to determine the creativity of teachers in overcoming the limitations of learning media. This study involved 24 fourth grade students as samples and collected data through observation and interview methods. Judging from the observations that have been made, teachers experience limitations in using learning media. However, the limitations of learning media are an obstacle in the learning process. Teachers are still required to be creative in the midst of existing limitations. From the research conducted, there is one way to increase teacher creativity in the midst of media limitations, namely using interactive powerpoint. Thus, it can be concluded that teachers are required to be creative by using interactive powerpoint in the midst of limited learning media.